Yeast ISO-1-Cytochrome C heme crevice polarity studied by second derivative spectroscopy. - Schroeder, H. (Concordia University, 1994)
Shows that second derivative spectroscopy is a good technique to monitor polarity changes associated with tyrosine residues in iso-1-cytochrome c.